Digital Muamalah and Economic Fairness: A Socio-Legal Analysis of FinTech Regulation in Muslim Countries - Asep Koswara (Presscience, 2026)
This socio-legal study addresses the central problem of economic fairness in digital mu’āmalah, investigating the tension between technological innovation, Sharia compliance, and consumer protection within FinTech regulation in Muslim countries. Employing a qualitative socio-legal methodology that contrasts doctrinal analysis of regulatory texts (OJK, BNM, DSN-MUI rulings) with assumed empirical data (stakeholder perceptions, public reports on consumer complaints), the research critically assesses the efficacy of current regulatory frameworks. The primary scientific finding reveals a